Aktualisasi Media Dakwah Instagram @santribatang - Mochamad Aris Yusuf; Fikriyatul Islami Mujahidah (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Da'wah messages can be broadcast through works called graphic design, as stated that graphic design is a form of visual communication that uses pictures along with sentences containing messages or characters in an informative and effective manner. This foundation is practiced by @santribatang conveying messages through Instagram social media. The purpose of this research is to find out how the da'wah built by the @santribatang account uses graphic design. The method used in this study is descriptive qualitative with the position of the researcher as the key instrument. The results obtained in this article indicate that the da'wah built by the Batang students uses the da'wah method which refers to Surah An-Nahl verse 125. Bil-hikmah with gentle delivery is far from being provocative. Wal mauizatul hasanah namely with advice, guidance and motivating learning to mad'u. Wa Jadilhum Bi al-Lati Hiya Ahsan with peaceful narrative content, but did not receive a response from mad'u namely the practice of discussion. It can be seen that the santri of Batang have implemented it well, but the lack of response from mad'u has the potential to cause misunderstandings. In fact, the effort to cheer mad'u is very important to note.